Pan-PPAR agonist IVA337 is effective in experimental lung fibrosis and pulmonary hypertension. Issue 11 (11th August 2017) - Avouac, Jerome; Konstantinova, Irena; Guignabert, Christophe; Pezet, Sonia; Sadoine, Jeremy; Guilbert, Thomas; Cauvet, Anne; Tu, Ly; Luccarini, Jean-Michel; Junien, Jean-Louis; Broqua, Pierre; Allanore, Yannick
Abstract : Objective: To evaluate the antifibrotic effects of the pan-peroxisome proliferator-activated receptor (PPAR) agonist IVA337 in preclinical mouse models of pulmonary fibrosis and related pulmonary hypertension (PH). Methods: IVA337 has been evaluated in the mouse model of bleomycin-induced pulmonary fibrosis and in Fra-2 transgenic mice, this latter being characterised by non-specific interstitial pneumonia and severe vascular remodelling of pulmonary arteries leading to PH. Mice received two doses of IVA337 (30 mg/kg or 100 mg/kg) or vehicle administered by daily oral gavage up to 4 weeks. Results: IVA337 demonstrated at a dose of 100 mg/kg a marked protection from the development of lung fibrosis in both mouse models compared with mice receiving 30 mg/kg of IVA337 or vehicle. Histological score was markedly reduced by 61% in the bleomycin model and by 50% in Fra-2 transgenic mice, and total lung hydroxyproline concentrations decreased by 28% and 48%, respectively, as compared with vehicle-treated mice. IVA337 at 100 mg/kg also significantly decreased levels of fibrogenic markers in lesional lungs of both mouse models. In addition, IVA337 substantially alleviated PH in Fra-2 transgenic mice by improving haemodynamic measurements and vascular remodelling. In primary human lung fibroblasts, IVA337 inhibited in a dose-dependent manner fibroblast to myofibroblasts transition induced by TGF-β and fibroblast proliferation mediated by PDGF. Conclusion: We demonstrate that treatment with 100 mg/kg IVA337 prevents lung fibrosis in two complementary animal models and substantially attenuates PH in the Fra-2 mouse model. These findings confirm that the pan-PPAR agonist IVA337 is an appealing therapeutic candidate for these cardiopulmonary involvements.